Application of microfluidic technology to pancreatic islet research: first decade of endeavor. (October 2010) - Wang, Yong; Lo, Joe F; Mendoza-Elias, Joshua E; Adewola, Adeola F; Harvat, Tricia A; Kinzer, Katie P; Lee, Dongyoung; Qi, Meirigeng; Eddington, David T; Oberholzer, José
Β-cells respond to blood glucose by secreting insulin to maintain glucose homeostasis. Perifusion enables manipulation of biological and chemical cues in elucidating the mechanisms of β-cell physiology. Recently, microfluidic devices made of polydimethylsiloxane and Borofloat glass have been developed as miniaturized perifusion setups and demonstrated distinct advantages over conventional techniques in resolving rapid secretory and metabolic waveforms intrinsic to β-cells. In order to enhance sensing and monitoring capabilities, these devices have been integrated with analytical tools to increase assay throughput. The spatio-temporal resolutions of these analyses have been improved through enhanced flow control, valves and compartmentalization. For the first time, this review provides an overview of current devices used in islet studies and analyzes their strengths and experimental suitability. To realize the potential of microfluidic islet applications, it is essential to bridge the gap in design and application between engineers and biologists through the creation of standardized bioassays and user-friendly interfaces.